Electrode Kinetic Studies of Mn(II) Complexes with Some Amino Acids(Glycine, a-Alanine and L-Valine) - Kumar, Suresh; Gupta, O.D. (Asian Journal of Chemistry, 2010)
Polarography was used to determine the stability constants (log b) and kinetic parameters of binary complexes of Mn(II) with glycine, a- alanine, L-valine at pH 8.30 ± 0.01 and ionic strength (μ) = 1 M KCl at 300 K. The reduction waves of Mn(II) and its complexes are quasireversible. The trend of stability constants of the complexes and electrode kinetic parameters have been evaluated.